1999
DOI: 10.1016/s0304-4203(99)00022-5
|View full text |Cite
|
Sign up to set email alerts
|

Low dissolved Fe and the absence of diatom blooms in remote Pacific waters of the Southern Ocean

Abstract: The remote waters of the Pacific region of the Southern Ocean are the furthest away from any upstream and upwind Ž continental Fe sources. This prime area for expecting Fe limitation of the plankton ecosystem was studied March-April . 1995 along a north-south transect at ; 898W. At the end of the austral summer the upper wind-mixed layers were in the order of ; 100 m deep, thus mixing the algae down into the dimly lit part of the euphotic zone where photosynthesis is severely restricted. The dissolved Fe was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
61
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(72 citation statements)
references
References 83 publications
11
61
0
Order By: Relevance
“…Owing to the silicic acid requirement of the diatom class, it dominates the ecosystem south of 50°S. To the north of the Antarctic Circumpolar Current, small phytoplankton dominate (consistent with observations [de Baar et al, 1999]). The modeled equatorial Pacific is richer in diatoms than observations suggest [Gregg et al, 2003], consistent with the upwelling of waters from too great a depth to the surface of this region (as discussed above).…”
Section: Chlorophyll and Primary Productivitysupporting
confidence: 83%
“…Owing to the silicic acid requirement of the diatom class, it dominates the ecosystem south of 50°S. To the north of the Antarctic Circumpolar Current, small phytoplankton dominate (consistent with observations [de Baar et al, 1999]). The modeled equatorial Pacific is richer in diatoms than observations suggest [Gregg et al, 2003], consistent with the upwelling of waters from too great a depth to the surface of this region (as discussed above).…”
Section: Chlorophyll and Primary Productivitysupporting
confidence: 83%
“…The higher values determined by Löscher et al (1997) in the Atlantic sector of the Southern Ocean are explained by the upwelling of iron rich Antarctic waters Apparent particulate iron (Fe app ) concentrations, calculated by subtracting DFe values measured during the cruise (Blain et al, 2008) from TDFe, are reported in Table 1. Fe app is defined as the iron adsorbed on lithogenic or biogenic particles, the biogenic iron and the labile lithogenic particulate iron (de Baar et al, 1999) plus the refractory colloids included in the dissolved fraction and that were not measured on board after a few days of acid storage. Fe app represents between 82 and 99% of the TDFe (mean value 95±5%) above the plateau and between 83 and 93% (mean value 86±3%) outside the plateau with no difference between surface and deep water (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…That fraction represents the sum of the dissolved iron (i.e. the labile dissolved iron which is the fraction that is released after a few days of acidification) plus the refractory colloidal iron (i.e., that fraction that dissolved after more than a few days of acidification) plus the fraction of particulate material that dissolves during extended (>6 months) acid storage (iron adsorbed on lithogenic or biogenic particles, contained within biogenic particles and labile lithogenic particulate iron) (de Baar et al, 1999;Löscher et al, 1997;Bowie and Sedwick, 2004). In the literature, the set of TDFe observations is much smaller than that of DFe.…”
mentioning
confidence: 99%
“…In the past decades, a large number of dFe measurements have been collected that provide seasonal variability data in the Southern Ocean (e.g., Martin et al, 1990;de Baar et al, 1995de Baar et al, , 1999Löscher et al, 1997;Lannuzel et al, 2011;Fitzwater et al, 2000;Sedwick et al, 1997Sedwick et al, , 1999Sedwick et al, , 2000Sedwick et al, , 2008Sedwick et al, , 2011Sohrin et al, 2000;Measures and Vink, 2001;Bowie et al, 2004Coale et al, 2005;Chever et al, 2010. However, despite these efforts, there are some months in different ocean regions and basins in which no dFe measurements have yet been made.…”
Section: Sampling Frequency and Seasonalitymentioning
confidence: 99%